2014
DOI: 10.1371/journal.pone.0112120
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Myocardin Expression by Tumor Necrosis Factor-α in Vascular Smooth Muscle Cells

Abstract: De-differentiation of vascular smooth muscle cells (VSMCs) plays a critical role in the development of atherosclerosis, a chronic inflammatory disease involving various cytokines such as tumor necrosis factor-α (TNFα). Myocardin is a co-factor of serum response factor (SRF) and is considered to be the master regulator of VSMC differentiation. It binds to SRF and regulates the expression of contractile proteins in VSMCs. Myocardin is also known to inhibit VSMC proliferation by inhibiting the NF-κB pathway, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Activation of myocardin transcriptional activity induces expression of the contractile genes and their proteins. Our previous study showed that overexpression of myocardin in human vascular SMCs through the T‐REx system increases contractility of SMCs (Jiang et al, ; Singh and Zheng, ). To determine whether the atrogin‐1 effects were mediated by an increase in myocardin transcriptional activity, we overexpressed the dominant‐negative (DN) myocardin in SMCs using the T‐REx system, as previously described (Jiang et al, ), before ad‐atrogin‐1 treatment and collagen gel lattice contraction assay.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of myocardin transcriptional activity induces expression of the contractile genes and their proteins. Our previous study showed that overexpression of myocardin in human vascular SMCs through the T‐REx system increases contractility of SMCs (Jiang et al, ; Singh and Zheng, ). To determine whether the atrogin‐1 effects were mediated by an increase in myocardin transcriptional activity, we overexpressed the dominant‐negative (DN) myocardin in SMCs using the T‐REx system, as previously described (Jiang et al, ), before ad‐atrogin‐1 treatment and collagen gel lattice contraction assay.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have also shown that NF-κB plays a direct role in regulating the expression of contractile VSMC genes. Activation of the NF-κB signalling pathway in VSMCs results in binding of the NF-κB-p65 subunit to the MYOCD promoter, decreasing the expression of myocardin and myocardin-dependent contractile genes (e.g., αSMA/ ACTA2, SM22α/TAGLN, and SMMHC/MYH11; Tang et al, 2008;Yoshida et al, 2013;Singh & Zheng, 2014). Together, these studies suggest that NF-κB inhibition, which specifically affects VSMCs could be a potential therapeutic target.…”
Section: Targeting Vsmc Inflammatory Activationmentioning
confidence: 88%
“…It was previously reported that PCSK9 is expressed in dedifferentiated vascular SMCs (Ding, Liu, Wang, Deng, Fan, Sun, et al, 2015; Z. H. Tang et al, 2019), but how PCSK9 induces SMC dedifferentiation is not completely understood. It is well‐known that activation of nuclear factor‐κB (NF‐κB) is critical for SMC dedifferentiation (Singh & Zheng, 2014; R. H. Tang et al, 2008). In macrophages, our group showed that PCSK9 overexpression activates the NF‐κB pathway (Z. H. Tang et al, 2017).…”
Section: Pcsk9 and Vascular Diseasementioning
confidence: 99%